THE ROLE OF CSR IN INCREASING LE MINERALE PURCHASE INTENTION: BRAND LOYALTY AND TRUST AS MEDIATORS - Aming Putri Agustin; Mirzam Arqy Ahmadi (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2025)
The global problem of micro plastics polluting the environment and the human food chain encourages companies, including Le Minerale, to demonstrate social responsibility through Corporate Social Responsibility (CSR). This study examines the effect of CSR on purchase intention of Le Minerale products, with brand loyalty and brand trust as mediators. The research employed a quantitative method utilizing purposive sampling. Data were gathered from 171 respondents in Java via an online survey featuring a Likert scale questionnaire (1-5) and analyzed using SEM-PLS with Smart PLS software version 3. The results indicate that CSR positively and significantly impacts brand loyalty and brand trust, which, in turn, mediate its influence on purchase intention. These findings align with prior studies emphasizing the role of CSR in fostering brand loyalty and trust to enhance consumer purchase intention. However, this study is limited to the geographical coverage of Java Island, so the results cannot be generalized to the national population.